2015
DOI: 10.1083/jcb.2087oia41
|View full text |Cite
|
Sign up to set email alerts
|

IgE-activated basophils regulate eosinophil tissue entry by modulating endothelial function

Abstract: Vertebrate immunity has evolved a modular architecture in response to perturbations. Allergic inflammation represents such a module, with signature features of antigen-specific IgE and tissue eosinophilia, although the cellular and molecular circuitry coupling these responses remains unclear. Here, we use genetic and imaging approaches in models of IgEdependent eosinophilic dermatitis to demonstrate a requisite role for basophils. After antigenic inflammation, basophils initiate transmigration like other granu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 31 publications
5
36
0
1
Order By: Relevance
“…Since this passive model relies on specific IgE antibodies, and not on IgG, these results strongly suggest that direct activation of basophils through FcεRI is responsible for the delayed allergic skin inflammation observed this model. Using a similar model of IgEmediated chronic allergic inflammation, Cheng et al also reported markedly reduced eosinophilic dermatitis in basophil-deficient mice as compared to control mice three days after cutaneous challenge with the relevant antigen (Cheng, Sullivan et al 2015).…”
Section: Anaphylaxismentioning
confidence: 95%
“…Since this passive model relies on specific IgE antibodies, and not on IgG, these results strongly suggest that direct activation of basophils through FcεRI is responsible for the delayed allergic skin inflammation observed this model. Using a similar model of IgEmediated chronic allergic inflammation, Cheng et al also reported markedly reduced eosinophilic dermatitis in basophil-deficient mice as compared to control mice three days after cutaneous challenge with the relevant antigen (Cheng, Sullivan et al 2015).…”
Section: Anaphylaxismentioning
confidence: 95%
“…Basophils infiltrate the skin in response to mechanical or immunologic stress and are key orchestrators in the recruitment of eosinophils to sites of allergic inflammation, a hallmark of atopic disorders. 22,23 In the context of food allergies, recent studies have demonstrated that ablation of basophil responses resulted in a significant decrease in recruitment of eosinophils to sites of antigen sensitization and protected mice from development of IgE-dependent and independent food-induced allergic disorders. 16,24,25 Given that both basophils and eosinophils are potent innate sources of IL-4 26 and that eosinophils often outnumber basophils at inflammatory sites, it is likely that basophilmediated infiltration of eosinophils to the skin might promote food antigen sensitization and the development of IgE-mediated food allergy.…”
Section: Eosinophils Are Dispensable For Both Epicutaneous Food Antigmentioning
confidence: 99%
“…When endothelium‐transmigrating basophils bound IgE, the cells slowed down and released IL‐4. This induced VCAM‐1 expression on endothelial cells and facilitated eosinophil influx . Hence, basophils might exacerbate to tissue eosinophilia.…”
Section: Introductionmentioning
confidence: 99%